2019
DOI: 10.1111/ctr.13582
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 high‐risk genotypes and renal transplantation

Abstract: The discovery of apolipoprotein L1 (APOL1) gene variants and its association with kidney disease in African-Americans represent a significant breakthrough in understanding the genetic basis of ancestry-based differences in a public health problem.The role these variants play in renal transplantation is still incompletely understood.This article reviews the epidemiologic data and current reports of APOL1 variant pathogenesis in transplantation. We examine existing data on outcomes in APOL1 high-risk kidneys, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The most compelling case for genetic testing of APOL1 in the clinical setting at present is therefore in kidney transplantation, particularly for potential living donors 64 , 65 . An ongoing NIH-funded study — the APOL1 Long-term Kidney Transplantation Outcomes study (APOLLO) — is aimed at prospectively determining outcomes in living kidney donors with African ancestry and in recipients of living and deceased donor kidneys from individuals with African ancestry, in order to better define the effect of APOL1 risk alleles on transplantation outcomes, and will provide data with which to guide patients and clinicians in judging the risk of transplantation for living donors and recipients 66 , 67 .…”
Section: Apol1 and Kidney Diseasementioning
confidence: 99%
“…The most compelling case for genetic testing of APOL1 in the clinical setting at present is therefore in kidney transplantation, particularly for potential living donors 64 , 65 . An ongoing NIH-funded study — the APOL1 Long-term Kidney Transplantation Outcomes study (APOLLO) — is aimed at prospectively determining outcomes in living kidney donors with African ancestry and in recipients of living and deceased donor kidneys from individuals with African ancestry, in order to better define the effect of APOL1 risk alleles on transplantation outcomes, and will provide data with which to guide patients and clinicians in judging the risk of transplantation for living donors and recipients 66 , 67 .…”
Section: Apol1 and Kidney Diseasementioning
confidence: 99%
“…Patients with African ancestry sustain a significantly higher risk of non-Mendelian focal segmental glomerulosclerosis (FSGS) as well as end stage kidney disease (ESKD) (reviewed in literature (1)). Seminal work identified the risk genotypes of Apolipoprotein L1 (APOL1) when present as two copies of either or both G1 and G2 alleles, (2) explained the increased risk of FSGS and ESRD observed in African Americans (AAs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also revealed that PENK is an important biomarker for renal dysfunction (42)(43)(44). In addition, APOL1, encoding a secreted high-density lipoprotein that binds to apolipoprotein A-I to promote lipid exchange, is reported to be associated with kidney disease when it is mutated (45). With regards to the interaction between the cardiovascular and renal systems, PenK and aPol1 are also of potential value for cardiac disease research (46).…”
Section: Discussionmentioning
confidence: 99%